Christian Perspective to Reconciliation in Luke 15:25-32 - Christopher Naseri (European Scientific Journal, ESJ, 2018)
Reconciliation is a process in conflict management, resolution and transformation. It sets the stage for the transformation of conflict and a postconflict coexistence. In societal confrontation with moral and political tensions that result from wrongdoing and conflict between persons or groups, reconciliation has variously been conceived of as an elusive concept. The questions often raised concern the possibility of genuine reconciliation between parties formerly at odds with one another and the ability of the victim to accept reconciliation with the aggressor. This work looks at reconciliation from a Christian perspective as an objective in the dynamics of mercy. This exercise of mercy is evident in the parable of the compassionate father in Luke 15. Using historical critical method in the study of Luke 15:25-32 the work reveals that the acknowledgement of an existing relationship between persons in situations of wrongdoings provides an enabling environment for the request for and granting of mercy. It recommends that emphasising, re-proposing, and improving on the relationship that existed prior to conflicts should constitute the process of facilitating reconciliation in the resolution of conflicts among persons or groups.